M2 polarization enhances silica nanoparticle uptake by macrophages - Hoppstädter, Jessica; Seif, Michelle; Dembek, Anna; Cavelius, Christian; Huwer, Hanno; Kraegeloh, Annette; Kiemer, Alexandra K. (Frontiers in Pharmacology, 2015)
While silica nanoparticles have enabled numerous industrial and medical applications, their toxicological safety requires further evaluation. Macrophages are the major cell population responsible for nanoparticle clearance in vivo. The prevailing macrophage phenotype largely depends on the local immune status of the host. Whereas M1-polarized macrophages are considered as pro-inflammatory macrophages involved in host defense, M2 macrophages exhibit anti-inflammatory and wound-healing properties, but also promote tumor growth. We employed different models of M1 and M2 polarization: GM-CSF/LPS/IFN-gamma was used to generate primary human M1 cells and M-CSF/IL-10 to differentiate M2 monocyte-derived macrophages. PMA-differentiated THP-1 cells were polarized towards an M1 type by LPS/IFN-gamma and towards M2 by IL-10. Uptake of fluorescent silica nanoparticles (Ø 26 and 41 nm) and microparticles (Ø 1.75 µm) was quantified. At the concentration used (50 µg/ml), silica nanoparticles did not influence cell viability as assessed by MTT assay. Nanoparticle uptake was enhanced in M2-polarized primary human monocyte-derived macrophages compared with M1 cells, as shown by flow cytometric and microscopic approaches. In contrast, the uptake of microparticles did not differ between M1 and M2 phenotypes. M2 polarization was also associated with increased nanoparticle uptake in the macrophage-like THP-1 cell line. In accordance, in vivo polarized M2-like primary human tumor-associated macrophages (TAM) obtained from lung tumors took up more nanoparticles than M1-like alveolar macrophages isolated from the surrounding lung tissue. In summary, our data indicate that the M2 polarization of macrophages promotes nanoparticle internalization. Therefore, the phenotypical differences between macrophage subsets should be taken into consideration in future investigations on nanosafety, but might also open up therapeutic perspectives allowing to specifically target M2 polarized macrophages.